From dusk till dawn: Attracting suppliers for resource mobilization during bankruptcy. Issue 3 (June 2019) - Wadell, Olof; Bengtson, Anna; Åberg, Susanne
Abstract: Changes in industrial systems increase the efforts needed to attract a counterpart for resource mobilization. The purpose of the article is to elaborate on the impact of customer attractiveness on supplier resource mobilization during radical changes such as bankruptcy. We use a case study method and focus on an extreme case of supplier resource mobilization, i.e. the study of mobilization during the bankruptcy process of a large company. We investigate how the bankruptcy estate managed resource mobilization necessary for maintaining the bankrupt company's facility from the time of declaration of bankruptcy until the facility could be sold to a new owner (from dusk till dawn), providing a detailed description of how the bankruptcy estate attracted suppliers despite the bankrupt company's previous losses. Our findings show that attractiveness is a valid theoretical tool in order to understand resource mobilization also in situations that lack social aspects of relationships. Furthermore, the study shows that resource embeddedness and knowledge transfer affect customer attractiveness and impact supplier resource mobilization. Finally, we demonstrate that even in settings characterized by relationship ending, both experience- and expectation-based attractiveness exist. Highlights: Study of the impact of customer attractiveness on supplier resource mobilization during radical changes such as bankruptcy. Studying attractiveness helps understanding resource mobilization in situations that lack established actor bonds. Resource embeddedness affects customer attractiveness and impacts supplier resource mobilization. Even in settings characterised by relationship ending, both experience- and expectation-based attractiveness exist. Customer attractiveness is both critical and complex in situations of radical change.